2020
DOI: 10.3390/jpm10030123
|View full text |Cite
|
Sign up to set email alerts
|

The Genomics and Metagenomics of Asthma Severity (GEMAS) Study: Rationale and Design

Abstract: Asthma exacerbations are a major contributor to the global disease burden, but no significant predictive biomarkers are known. The Genomics and Metagenomics of Asthma Severity (GEMAS) study aims to assess the role of genomics and the microbiome in severe asthma exacerbations. Here, we present the design of GEMAS and the characteristics of patients recruited from March 2018 to March 2020. Different biological samples and demographic and clinical variables were collected from asthma patients recruited by allergy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…A total of 257 saliva, 232 pharyngeal, and 229 nasal samples from European individuals with asthma from the Genomics and Metagenomics of Asthma Severity (GEMAS) study were analyzed in the discovery phase. 9 Their main demographic and clinical characteristics are summarized in Table I . Briefly, subjects had a median age of 39.0 years (interquartile range, 18.0-59.0 years) and 61.5% were female.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 257 saliva, 232 pharyngeal, and 229 nasal samples from European individuals with asthma from the Genomics and Metagenomics of Asthma Severity (GEMAS) study were analyzed in the discovery phase. 9 Their main demographic and clinical characteristics are summarized in Table I . Briefly, subjects had a median age of 39.0 years (interquartile range, 18.0-59.0 years) and 61.5% were female.…”
Section: Resultsmentioning
confidence: 99%
“…A full description of the study design, eligibility criteria, and characteristics of enrolled subjects is reported elsewhere. 13 Briefly, European patients aged between 8 and 85 years with a diagnosis of asthma based on the Global Initiative for Asthma (GINA) 2020 guidelines 3 were recruited in several allergy and respiratory medicine hospital units in Spain. GEMAS was approved by the ethics committees of participant centers (approval nos.…”
Section: Study Populationmentioning
confidence: 99%
“…Within the Genomics and Metagenomics of Asthma Severity (GEMAS) project [ 189 ], which included 250 asthmatic patients treated with ICS, our group studied the association between the salivary, pharyngeal, and nasal microbiome with asthma exacerbations, wherein it was observed that, in nasal and saliva samples, those who had presented moderate or severe exacerbations (use of OCS and/or hospital admission) had less bacterial diversity than those who did not present exacerbations [ 190 ]. Exacerbations accounted for 8% to 9% of the interindividual variation in the salivary and nasal microbiomes, respectively.…”
Section: Future Guidelinesmentioning
confidence: 99%